Cultural Influences on Accounting Practices and Financial Disclosure Choices (gjstudies, 2026)
This research investigates the profound and often underappreciated influence ofnational culture on the fundamental practices of accounting and the strategic choicessurrounding financial disclosure. Moving beyond traditional economic and institutionalexplanations, this paper posits that deeply embedded cultural dimensions—specificallythose articulated by Hofstede, such as individualism versus collectivism, power distance, uncertainty avoidance, and long-term orientation—act as primary, yet informal,institutional forces shaping how financial information is measured, recognized, presented, and communicated. The study employs a novel, multi-methodological framework that combines a qualitative, interpretative analysis of accounting standard-settingnarratives with a quantitative, large-N panel data analysis of disclosure practices across42 countries from 1995 to 2005. The qualitative component deconstructs the discourseand compromise inherent in international accounting convergence efforts, revealing howcultural conflicts are sublimated into technical accounting language. The quantitativemodel innovatively treats cultural scores as time-invariant, deep determinants that interact with formal legal and economic variables to predict the quality, quantity, andtimeliness of corporate disclosures. Our findings reveal that high uncertainty avoidancecultures are associated with more conservative earnings measurements and a preferencefor rules-based standards, while high individualism correlates with greater transparencyand forward-looking disclosures. Collectivist societies, conversely, demonstrate a higherreliance on private information channels and relationship-based disclosure, often at theexpense of public transparency. A particularly significant and original finding is theidentification of a cultural compliance threshold, where the effectiveness of imported,culturally-alien accounting standards (e.g., IFRS adoption in high power-distance countries) diminishes markedly unless accompanied by congruent shifts in underlying informal institutions. The paper concludes that a purely technical, de-contextualizedapproach to global accounting harmonization is fundamentally flawed. Recognizingculture as a constitutive element of accounting practice, rather than mere backgroundnoise, offers a more robust framework for policymakers, standard-setters, and multina1tional corporations to navigate the complexities of global financial reporting, predictcross-border misunderstandings, and design more effective, culturally-resonant disclosure regimes